The development of strain anisotropy during plastic deformation of an aluminium polycrystal - Korsunsky, A; Daymond, MR; Wells, K (Trans Tech Publ, 2000)
To measure internal strains in an Al MMC, time-of-flight (TOF) ncutron diffraction was used on the ENGIN instrument at ISIS, RAL, in Oxfordshire, and a monochromated X-ray beam was employed on the BM16 beamline at the ESRF in Grenoble. The development of intergranular stresses between groups of grains possessing certain crystallographic orientations was studied using diffraction of penetrating radiation. Due to aluminum's highly isotropic elastic modulus, the variation of measured strains in the alloy matrix with orientation can be attributed to the anisotropy of the crystal yield surface and plastic flow parameters. A simple illustrative model is presented which explains the observed correlation between the amount of plastic strain (PS) and the measured anisotropy strain (AS) values. In particular, the model explains why a linear relationship is observed between AS and PS for low strain values, and how saturation of AS sets in at higher imposed PS levels.